Considerations on Immunization and Immunosuppression of Patients With Autoimmune Blistering Diseases During COVID-19 Pandemic in Brazil: Case Report - Miyamoto, Denise; Santi, Claudia Giuli; Maruta, Celina Wakisaka; Aoki, Valeria (Frontiers in Medicine, 2022)
Autoimmune blistering diseases comprise a rare group of potentially life-threatening dermatoses. Management of autoimmune disorders poses a challenge in terms of achieving disease control and preventing adverse events. Treatment often requires an individualized approach considering disease severity, age, comorbidities, and infectious risk especially in the context of the ongoing COVID-19 pandemic. Knowledge regarding SARS-CoV-2 infection is still evolving and no specific antiviral therapy is available yet. We report four patients with active disease that required adjustment of treatment during the pandemic to discuss the use of immunosuppressants and immunobiologics, weighing potential risks and benefits of each therapy modality and vaccination status.